Ludicidade na educação infantil: influência no processo de formação integral, na escola Padre Arrupe/PI, na perspectiva da Pedagogia Inaciana - Paula, Jorge Luiz de (Universidade do Vale do Rio dos Sinos, 2019)
Play is a factor that makes the child active in his own learning process, which allows the construction of autonomy and solidifies relations with the environment and with others, creating bonds of trust and satisfaction, enabling significant gains in integral development. The objective of this research is to identify how playfulness, in the perspective of integral formation, considering the principles of the Ignatian Pedagogy, has developed within the scope of the Padre Arrupe School, located in the city of Teresina-PI. In this way, a bibliographical and documentary research, of exploratory and qualitative character, was used. As for the objectives, the research is classified as exploratory and explanatory. It was tried to use, as theoretical base, authors that directed its line of research to the presented theme. They are: Flecha (2009); Kramer (2003); Piaget (1990); Kishimoto (2012); Klein (2015). The results show that all understanding about Early Childhood Education leads to the discourse that playfulness is fundamental in the formation of the child and that both in the educational and social spheres, the play influences in a decisive way in the construction of the values that are being established and solidifying fundamental principles for the formation of conscious, competent, compassionate, committed and creative people before the current social scene.
Keywords: Formação integral; Ludicidade; Educação infantil; Pedagogia inaciana; Integral training; Playfulness; Child education; Ignatia pedagogy